Impact of climate change on ruminant health and Emerging Diseases in Egypt - Kassem, Ashraf; Khattab, Marwa S.; Ismael, Elshaimaa; Osman, Ahmed H. (Journal of applied veterinary sciences, 2025)
Climate change is one of the biggest risks to animal health. Although extensive livestock production was one of the major contributing causes of this change. Egypt’s climate has unique factors that are influenced by its geographic position. The average temperature throughout the year, relative humidity and heat waves in Egypt were escalating, especially in Upper Egypt. There is a direct and indirect link between climate change and animal diseases, which present as a serious health threat. Ruminants are stressed by meteorological changes, which lower their immunity and make them more susceptible to infections. In ruminant animals, climate change can lead to higher temperatures and humidity levels that facilitate the reproduction, survival, and transmission of certain bacteria, viruses, and parasites that cause diseases. In livestock production, heat stress (HS) is a major stressor as it acts as a severe climate shock. Multiple weather variables contribute to the adverse effects of HS, such as high ambient temperatures, humidity, solar radiation, and wind speeds, which negatively impact animal welfare and productivity. The aim of this review article is to summarize the current state of knowledge regarding the influence of climate and climate change on the health of food-producing cattle and sheep as well as explore its potential relationship with increased incidence of ill bleeding, jaundice and feverish cases in slaughtered animals.